2013
DOI: 10.3171/2013.3.jns121865
|View full text |Cite
|
Sign up to set email alerts
|

In vivo embolization of lateral wall aneurysms in canines using the liquid-to-solid gelling PPODA-QT polymer system: 6-month pilot study

Abstract: Object Over the past 20 years, endovascular embolization has become the preferred method of treating cerebral aneurysms. While there are many embolic devices on the market, none is ideal. In this study the authors investigated the use of a liquid-to-solid gelling polymer system—that is, poly(propylene glycol) diacrylate and pentaerythritol tetrakis (3-mercaptopropionate) (PPODA-QT)—to embolize in vivo aneurysms over a 6-month period. Methods Experimental aneurysms were created in the carotid arteries of 9 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 39 publications
(33 reference statements)
0
33
0
Order By: Relevance
“…Proof of concept was confirmed in vivo using a canine model with surgically induced aneurysms in the lateral wall of the carotid artery [130]. PPODA and QT were combined in a 2:1 molar ratio to create a hydrophobic monomer solution.…”
Section: Research and Development Of Advanced Materialsmentioning
confidence: 99%
“…Proof of concept was confirmed in vivo using a canine model with surgically induced aneurysms in the lateral wall of the carotid artery [130]. PPODA and QT were combined in a 2:1 molar ratio to create a hydrophobic monomer solution.…”
Section: Research and Development Of Advanced Materialsmentioning
confidence: 99%
“…In the past decade, various alternative embolic agents with improved packing density including hydrogel-coated coils (Taschner et al, 2018), shape memory polymer foams (Rodriguez et al, 2012;Horn et al, 2017) and in situ forming hydrogels have been reported (Takao et al, 2006;Barnett et al, 2009;Ishikawa et al, 2012;Bearat et al, 2013;Brennecka et al, 2013;Brady et al, 2017). Photopolymerizable hydrogels provide better spatial and temporal control over curing compared to hydrogels responsive to chemical, temperature or pH stimuli (Corrigan et al, 2019) and allow to fill any shapes in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral aneurysms are found in 45 million individuals worldwide, and approximately 30,000 patients in the United states suffer from subarachnoid hemorrhage annually. [ 6 ] Following several clinical trials demonstrating the benefits of coil embolization, endovascular techniques for aneurysm treatment have been increasingly applied to a wide array of both ruptured and unruptured aneurysms. For larger aneurysms and particularly those with wide-neck dome-to-neck ( d: n ) ratios, coil embolization still poses significant challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In lieu of a porous network of coils or a metal mesh that only partially blocks flow in an aneurysm, PPODA-QT can completely fill the aneurysm volume with a mass that is both solid and stable. [ 6 ] PPODA-QT may confer improved delivery control, vessel protection, and reduced recanalization rates in larger aneurysms with medium- to wide-necks [ Figure 1 ]. [ 6 , 7 , 25 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation